Characterization of galloylated cyanogenic glucosides and hydrolysabletannins from leaves of Phyllagathis rotundifolia by LC-ESI-MS/MS - Chuah, C.H.; Tan, H.P.; Ling, S.K. (John Wiley & Sons, Ltd., 2011)
Introduction: Phyllagathis rotundifolia (Jack) Bl. (Melastomataceae) is a creeping herb found in Peninsular Malaysia and Sumatra. Traditionally, a decoction of the leaves is used in the treatment of malaria, fever and stomach ache. Objective:To provide ESI‐MSⁿ data which are applicable for chemical fingerprinting of P. rotundifolia to obviate laborious isolation and purification steps.